Quantitative computed tomography is a novel diagnostic tool for early scrutiny of osteopenia and/or osteoporosis - Uppal, Rizwan (International Journal of Pathology, 2023)
Background: Osteoporosis is a significant public health concern, particularly affecting women. Accurate diagnosis of osteoporosis is crucial for early intervention. This study aimed to evaluate the effectiveness of Quantitative Computed Tomography (QCT) and Dual-Energy X-ray Absorptiometry (DXA) scans in individuals suspected of having osteoporosis. Methods: A cross-sectional study was conducted at the Islamabad Diagnostic Centre from June 2022 to June 2023. Participants suspected of having osteoporosis were recruited and underwent QCT and DXA scans. QCT evaluated inner trabecular bone, while DXA assessed bone mineral density (BMD). Diagnostic findings were compared. Results: Of the participants, 89.3% had lower average QCT-T scores than DXA-T scores. QCT detected osteopenia in 96.6% and osteoporosis in 57.1% of subjects, while DXA identified osteopenia in 65% and osteoporosis in 10.7%. QCT demonstrated early detection potential, particularly for osteoporosis. Conclusion: QCT is a reliable tool for early diagnosis of osteopenia and osteoporosis, as it accurately assesses inner spongy trabecular bone. It offers advantages over DXA, including cost-effectiveness in low- and middle-income countries. Global health strategies should prioritize osteoporosis assessment, considering the findings of this study